Exploration of Suitability of Situational Leadership in the Oil and Gas Sector - Ebere, Eberechukwu; Fragouli, Evangelia (Journal of Social Economics Research, 2015)
The purpose of this study was to investigate whether managers in Nigerian Oil and Gas companies exhibit situational leadership style, flexibility and adjustment to different situations. This study also investigated the validity of the Situational Leadership model, examining the relationship between employee maturity and leaders tolerance for autonomy. To identify a leader’s observed leadership style and a follower’s preferred leadership style, the Leadership Effectiveness and Adaptability Description (LEAD) – Other Instrument was used. The researcher used secondary sources (literature review) in order to analyze in more depth the data selected. Connections with theory and practice were made through the main theoretical lenses of leadership theory, particularly leadership style theory and situational leadership. Reference was also made to the context and nature of the oil and gas industry, as well as, to the influence of national culture on worker orientation.